FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN KELUARGA SEKTOR KESEHATAN DI BURSA EFEK INDONESIA - Christiana, Jesslyn; Cahyadi, Hadi (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This research aims at understanding the role of capital structure. liquidity, and growth on firm value mediated by profitability on healthcare sector family business listed on the Indonesia Stock Exchange during 2019-2022. Sample was selected using the method purposive sampling and number of firms used as samples amount to 9 firms. Data was processed using PLS-SEM analysis on data processing application SmartPLS 4.0.9.3 and Microsoft Excel 2013. The results of this study indicate that capital structure, liquidity and profitability has positive significant effect, while growth has negative insignificant effect on firm value. Profitability is able to mediate relationship between liquidity and growth on firm value, but not between capital structure on firm value. The implication of this study is the need of adequate capital structure, liquidity and profitability management in healthcare sector family businesses for those are the main factors affecting firm valuation.